Devonian porphyry Cu deposits in NW China: the Xiaotuergen example. Issue 10 (27th July 2017) - Geng, Xinxia; Yang, Fuquan; Qin, Jihua; Wen, Chaoquan
ABSTRACT: The Nuoerte Basin in northern Altay contains numerous mineral discoveries, including the Xiaotuergen porphyry Cu, Kumasu VMS Pb–Zn, and Hongshanzui orogenic Au deposits. This deposit, newly discovered by the 4th Geological Team of XJBGMR – the Xiaotuergen porphyry Cu deposit – is mainly hosted along the contact zone between the granodiorite porphyry and the Nuoerte Formation volcanic-sedimentary rocks. Disseminated, veinlet, veinlet-disseminated, and stockwork Cu mineralization occur in the granodiorite porphyry. Wall-rock alteration styles include mainly potassic (K-feldspar and biotite), silicic, carbonate, sericite, pyrite, chlorite, and epidote alterations. In this study, we used LA-ICP-MS zircon dating for the various rock types in the Xiaotuergen Cu ore district. The tuff at the periphery of the ore district has been newly dated to be ca. 411 Ma. This, together with stratigraphic correlation, suggests that the local stratigraphy is the Lower Devonian Nuoerte Formation, rather than the Lower Carboniferous Hongshanzui Formation as previously assumed. The ore-hosting granodiorite porphyry, quartz porphyry, biotite monzogranite, and granite porphyry are dated to be ca. 405 Ma, 400 Ma, 398 Ma, and 397 Ma, respectively. This constrains the Cu mineralization to be slightly younger than 405 Ma, and indicates that they may have belonged to the same Early Devonian intrusive event. Magmatism at Xiaotuergen had recommenced in the Late Devonian, as represented by minor granite porphyry dikes (ca. 370 Ma) intruding the ore-hosting granodiorite porphyry.